Code Mixing Analysis in English Teaching Learning Process at Senior High School 11 Pandeglang : Literatur Review - Yuyun Hasanati (Universitas Mathla'ul Anwar Banten, 2024)
This article examines the role of code mixing in English language teaching, specifically focusing on teachers' perceptions of its application in the classroom. Code mixing, the blending of two languages in discourse, takes various forms, including intra-sentential, intra-lexical, and pronunciation changes. Through a systematic literature review of five selected articles (2018-2023), the research highlights the prevalence of code mixing in Indonesian English classrooms due to factors like limited vocabulary and global influences. Teachers and students predominantly utilize intra- sentential code mixing for clarity, while intra-lexical and pronunciation changes are less frequent. Despite potential challenges leading to miscommunication, teachers view code mixing positively, considering it a valuable tool for enhancing student participation, comprehension, and vocabulary development. The study concludes that code mixing plays a crucial role in supporting English language learning, emphasizing its multifaceted nature and contributing to discussions on language, education, and sociolinguistic dynamics